Association between maternal vascular murmur and the small‐for‐gestational‐age fetus with abnormal umbilical artery Doppler flow. Issue 2 (7th August 2017) - Riknagel, Diana; Farlie, Richard; Hedegaard, Morten; Humaidan, Peter; Struijk, Johannes J.
Abstract: Objective: To investigate the association between maternal vascular murmurs (MVMs) and fetal growth restriction (defined as small‐for‐gestational‐age [SGA] fetus) and abnormal Doppler pulsatility index (PI) of the uterine and/or umbilical arteries. Methods: A cross‐sectional study of women aged 18 years or older with a singleton pregnancy at 28–34 weeks was conducted at Regional Hospital Viborg, Denmark, between May 1 and August 1, 2013. Ultrasound fetal biometry was performed and the Doppler PI of the umbilical and uterine arteries was determined. An estimated fetal weight (EFW) at or below the 10th percentile was defined as SGA. Microphone recordings from the lower abdomen were divided into heart valve sounds and MVMs. Results: The final analysis included 63 participants, with 25 classified as SGA and 38 as non‐SGA. The mean pregnancy duration was 32.4 ± 1.4 weeks. In total, 17 participants had MVMs. There was a clear association between MVMs and a composite of SGA and an abnormal PI of the uterine and/or the umbilical artery ( P< 0.001), but not between MVMs and SGA only ( P= 0.154). Conclusion: Maternal vascular murmurs are significantly associated with fetal growth restriction, but not with SGA per se. Abstract : Maternal vascular murmurs are significantly associated with fetal growth restriction, but not with small for gestational age per se.